В таблице.
Объяснение:
Заполнить таблицу:
a b c
4х²+5х-4=0 4 5 -4 Полное квадратное уравнение
-6х²+х+3=0 -6 1 3 Полное квадратное уравнение
15х-х²=0 -1 15 0 Неполное квадратное уравнение
7х²=0 7 0 0 Неполное квадратное уравнение
3х-х²+19=0 -1 3 19 Полное квадратное уравнение
2х²-14=0 2 0 -14 Неполное квадратное уравнение
2/3 х²-2х=0 2/3 -2 0 Неполное квадратное уравнение
х²+2-х=0 1 -1 2 Полное квадратное уравнение
1) 12a³ - a² + 6a - 1 = (12a³ + 6a) + ( - a² - 1)
2) 12a³ - a² + 6a - 1 = ( 12a³ - 1) - ( a² - 6a)